Structural insight into MtmC, a bifunctional ketoreductase-methyltransferase involved in the assembly of the mithramycin trisaccharide chain - Chen, Jhong Min (Biochemistry, 2015)
More and more post-PKS tailoring enzymes are recognized to be multifunctional and co-dependent on other tailoring enzymes. One of the recently discovered intriguing examples is MtmC, a bifunctional TDP-4-keto-d-olivose ketoreductase-methyltransferase, which – in co-dependence with glycosyltransferase MtmGIV – is a key contributor to the biosynthesis of the critical trisaccharide chain of the antitumor antibiotic mithramycin (MTM), produced by Streptomyces argillaceus. We report crystal structures of three binary complexes of MtmC with its methylation co-substrate SAM, its co-product SAH, and a nucleotide TDP as well as crystal structures of two ternary complexes, MtmC-SAH-TDP-4-keto-d-olivose and MtmC-SAM-TDP, in the range of 2.2-2.7 Å in resolution. The structures reveal general and sugar-specific recognition and catalytic structural features of MtmC. Depending on the catalytic function that is carried out by MtmC, it must bind either NADPH or SAM in the same co-factor binding pocket. A tyrosine residue (Tyr79) appears as a lid covering the sugar moiety of the substrate during the methyl transfer reaction. This residue swings out of the active site by about 180° in the absence of the substrate. This unique conformational change likely serves to release the methylated product and, possibly, to open up the active site for binding the bulkier co-substrate NADPH prior to the reduction reaction.